MRSA in conventional and alternative retail pork products. - Ashley M O'Brien; Blake M Hanson; Sarah A Farina; James Y Wu; Jacob E Simmering; Shylo E Wardyn; Brett M Forshey; Marie E Kulick; David B Wallinga; Tara C Smith (PLoS ONE, 2012)
In order to examine the prevalence of Staphylococcus aureus on retail pork, three hundred ninety-five pork samples were collected from a total of 36 stores in Iowa, Minnesota, and New Jersey. S. aureus was isolated from 256 samples (64.8%, 95% confidence interval [CI] 59.9%-69.5%). S. aureus was isolated from 67.3% (202/300) of conventional pork samples and from 56.8% (54/95) of alternative pork samples (labeled "raised without antibiotics" or "raised without antibiotic growth promotants"). Two hundred and thirty samples (58.2%, 95% CI 53.2%-63.1%) were found to carry methicillin-sensitive S. aureus (MSSA). MSSA was isolated from 61.0% (183/300) of conventional samples and from 49.5% (47/95) of alternative samples. Twenty-six pork samples (6.6%, 95% CI 4.3%-9.5%) carried methicillin-resistant S. aureus (MRSA). No statistically significant differences were observed for the prevalence of S. aureus in general, or MSSA or MRSA specifically, when comparing pork products from conventionally raised swine and swine raised without antibiotics, a finding that contrasts with a prior study from The Netherlands examining both conventional and "biologic" meat products. In our study spa types associated with "livestock-associated" ST398 (t034, t011) were found in 26.9% of the MRSA isolates, while 46.2% were spa types t002 and t008--common human types of MRSA that also have been found in live swine. The study represents the largest sampling of raw meat products for MRSA contamination to date in the U.S. MRSA prevalence on pork products was higher than in previous U.S.-conducted studies, although similar to that in Canadian studies.